Influence of Eu3+ Ions on Elastic Moduli and Microhardness of Zinc‑boro‑soda‑lime‑silica Glass System - Cheong, Wei Mun; Mohd Zaid, Mohd Hafz; Matori, Khamirul Amin; Fen, Yap Wing; Tee, Tan Sin; Loh, Zhi Wei; Mayzan, Mohd Zul Hilmi (Springer, 2024)
This study focuses on zinc-boro-soda-lime-silica (ZnO− B2O3−SLS) glasses produced through fast-cooling melt-quenching. The influence of Eu3+ ions on glass properties is explored. As Eu3+ concentration rises, bulk density and molar volume increase from 3.423 to 3.484 g/cm3 and 21.760 to 23.768 cm3 /mol, respectively. X-ray diffraction indicates amorphous phase dominance supported by glassy surface morphology. Ultrasonic measurements show the increasing and decreasing trend for ultrasonic velocities and elastic moduli with increasing Eu3+ concentration. Poisson’s ratio of the samples signifes their low cross-link density behavior. Moreover, the ZBS-3Eu presents the highest microhardness value of 4.776 GPa. The sample’s fractal bond connectivity varies from 1.814 to 2.051, suggesting a 2D structure. Likewise, the ZBS-3Eu glass sample exhibits the most rigidity attributed to its highest fg value of 0.075. These findings suggest that ZBS-3Eu has the potential for applications requiring high-strength glass.